Nilai Pendidikan Akidah Akhlak Di Madrasah Ibtidaiyah (Kajian Tafsir Surah Luqman Ayat 12 – 15) - Erma Sauva Asvia (Institut Agama Islam Darul Ulum Kandangan, 2022)
Abstract : This study suggests about the value of moral aqidah education in Madrasah Ibtidaiyah contained in Surah Luqman verses 12-19, This study aims to obtain an overview of the educational value of morals contained in Surah Luqman verses 12-19 which examines the Tafsir Ath-Thabari. The type of research used is library research by examining library materials related to the subject matter of the study by reading and studying books or other written sources that are relevant to the research title contained in the library sources. Through library research, the results of this study are as follows: First, Akhlak Akidah Education is teaching that can direct students to be able to get used to having noble character. Second, the value of moral aqidah education in Madrasah Ibtidaiyah generally contains values ??about faith and belief in order to stick to Islam and only believe in Allah SWT. as well as commendable in everyday life. Third, Luqman's teaching to his children who can be used as role models in the teaching process at school and at home. Keywords: Aqidah morals, Educational values, Surah Luqman Abstrak: Penelitian ini mengemukakan tentang nilai pendidikan akidah akhlak di Madrasah Ibtidaiyah yang terkandung dalam surah Luqman ayat 12-19, Penelitian ini bertujuan untuk memperoleh gambaran terhadap nilai pendidikan akidah akhlak yang terkandung dalam surah Luqman ayat 12-19 yang mengkaji pada Tafsir Ath-Thabari. Jenis penelitian yang digunakan adalah penelitian kepustakaan (Library Research) dengan meneliti bahan-bahan kepustakaan yang berkaitan dengan pokok masalah penelitian dengan membaca dan menelaah buku-buku atau sumber tertulis lainnya yang relevan dengan judul penelitian yang terdapat dalam sumber pustaka. Melalui penelitian kepustakaan (Library Research), maka hasil penelitian ini sebagai berikut: Pertama, Pendidikan Akidah Akhlak merupakan pengajaran yang dapat mengarahkan peserta didik untuk dapat membiasakan berakhlak mulia. Kedua, Nilai pendidikan akidah akhlak di Madrasah Ibtidaiyah secara garis besar mengandung nilai tentang keimanan dan keyakinan agar tetap berpegang teguh pada Agama Islam dan hanya beriman kepada Allah SWT. serta berakhlak terpuji pada kehidupan sehari-hari. Ketiga, Pengajaran Luqman kepada anaknya yang dapat dijadikan teladan dalam proses pengajaran disekolah maupun dirumah. Kata Kunci: Akidah akhlak, Nilai Pendidikan, Surah Luqman.